Gender analysis to inform the development of gender transformative approaches to enhance women's land rights in Kyrgyzstan - Ibraeva, Gulnara; Ablezova, Mehrigiul; Danshina, Anastasiia; Elias, Marlene (2023)
The Resilience of Organisations for Transformative Smallholder Agriculture Project (ROOTS) project was engaged as a co-financing mechanism as per the Gambia National Agricultural Investment Plan-Food and Nutrition Security (GNAIP-FNS II, 2017-2026) - to address the government’s priority concerns including account deficits, public services, population growth, outmigration of youth, agricultural productivity, climate change and environmental degradation, with the support of the International Fund for Agricultural Development (IFAD).